2006
DOI: 10.1021/jp0648083
|View full text |Cite
|
Sign up to set email alerts
|

Photostability of Colloidal PbSe and PbSe/PbS Core/Shell Nanocrystals in Solution and in the Solid State

Abstract: The photostability of semiconductor PbSe nanocrystals (NCs) under different storage conditions and the photoluminescence of PbSe NC films on Si substrates under vacuum and under different atmospheres were investigated. The NCs show a small blue shift in both the emission and absorption spectra when stored in solution. This blue shift is accelerated when the particles are stored in room light compared to when the particles are stored in the dark, which indicates that photooxidation is an important process. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(148 citation statements)
references
References 36 publications
11
135
2
Order By: Relevance
“…In contrast, our previously reported temperature-dependent PL studies [8] using ≈4-nm-diameter PbSe QDs produced in a similar manner [9,12,13], but with less control over the exposure of the samples to air during synthesis, exhibit monotonic, pure Arrhenius-like decay of integrated PL from 5 to 295 K, and detailed lineshape fits of spectra obtained from several batches over the entire temperature range of 5 to 295 K were consistent with only a single radiative transition.…”
Section: Introductioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast, our previously reported temperature-dependent PL studies [8] using ≈4-nm-diameter PbSe QDs produced in a similar manner [9,12,13], but with less control over the exposure of the samples to air during synthesis, exhibit monotonic, pure Arrhenius-like decay of integrated PL from 5 to 295 K, and detailed lineshape fits of spectra obtained from several batches over the entire temperature range of 5 to 295 K were consistent with only a single radiative transition.…”
Section: Introductioncontrasting
confidence: 64%
“…* young@phas.ubc.ca Previously we independently reported that the PL from these samples degraded at room temperature under exposure to oxygen [13], but that this effect was entirely reversible.…”
Section: Introductionmentioning
confidence: 99%
“…7 Different mechanisms were proposed to explain the PL enhancement but its nature still remains controversial due to the strong dependence of the NCs emissive properties on their surface quality, [3][4][5] as well as on the excitation intensity, 5-8 film morphology, 4,8,9 substrate-NCs interactions, 4,10 and environmental conditions. [11][12][13][14][15] The PL enhancement ͑PLE͒ has not been reported previously for PbSe NCs. This type of NCs became very attractive over the last few years as ͑near͒ infrared emitters because of the well controlled liquid-synthesis procedures developed recently 15,16 and the very large Bohr radius ͑46 nm͒ allowing for fine tuning and control of their optical properties.…”
mentioning
confidence: 65%
“…Figure 1 shows a typical example of a gold-terminated surface covered with densely packed HNCs that was observed either with scanning electron microscopy (SEM) or with scanning tunneling microscopy. As PbSe nanocrystals are known to suffer from a reduction in the quantum yield with time due to the oxidation of the nanocrystal surface, 24 the samples were kept, as often as possible, in a vacuum vessel, in particular, during the transfer between the different experimental systems used for their characterization.…”
Section: Methodsmentioning
confidence: 99%